Pengaruh Beban Kerja, Lingkungan Kerja dan Kompensasi Terhadap Kinerja Dosen Universitas Jabal Ghafur - Zulkifli Zulkifli (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2016)
The performance of a lecturer at a university is influenced by several variables. This research was conducted at Jabal Ghafur University using three variables; workload, working environment and compensation towards the performance of the lecturers of Jabal Ghafur University. The objective of the research was to find out the effect of workload, working environment and compensation towards the performance of the lecturers. Data were collected by distributing questionnaires to 120 lecturers of Jabal Ghafur University. Analytical tool used in this study to measure its effect was multiple linear regression analysis. The results showed that simultaneous workload, working environment, and compensation affect the performance of the lecturers and the effect is significant at 5% df. Correlation of independent variables on the dependent variable was perfect and determination coefficient stated that workload, working environment and compensation revealed that the performance of the lecturers of Jabal Ghafur University was 90.8%. It can be concluded that workload, working environment and compensation had a significant effect and it is suggested that the lecturers should be given opportunity to continue their study to a higher level.Keywords: Workload, Working Environment, Compensation,Lecturers’ Performance